ДОВІРА ЯК ІНСТИТУЦІЯ РОЗВИТКУ БІЗНЕСУ В УМОВАХ НОВИХ СОЦІАЛЬНИХ ВИКЛИКІ - Kyfyak, Viktoria; Filipchuk, Natalia (Інвестиції: практика та досвід, 2023)
У статті досліджено феномен "довіри в бізнесі" з позицій системного погляду. як базисної інституції у відносинах між суб'єктами економічних відносин. Описано полівекторне значення довіри для розвитку бізнесу. Визначено функції довіри як інституції бізнес-середовища та її важливість у формуванні комунікаційних зв'язків, як внутрішніх, так і зовнішніх. Охарактеризо вано особливість інституції довіри як регулятора соціально-економічної взаємодії бізнесу. Роз глянуто різні типи взаємозв'язків, які формують довіру, в інституційній архітектоніці, на основі чого зроблено висновок про системоутворюючий вплив довіри на інституційне середовище розвитку бізнесу. Систематизовано різні методики оцінювання рівня розвитку довіри в бізнесі та на основі досліджень ставлення до криптовалюти як нової інституції описано складові довіри в умовах циф ровізації. Досліджено інструменти розвитку інституції довіри та соціально-економічні ефекти від застосування інструментів розвитку довіри в інституційній взаємодії бізнесу в умовах флуктуацій.
TRUST AS AN INSTITUTION OF BUSINESS DEVELOPMENT IN THE NEW SOCIAL CHALLENGE CONDITIONS
Today's socio-economic challenges, which are exacerbated by uncertainty and fluctuations, have fundamentally complicated the relations of economic entities and business connections around the world. Communications that were guaranteed by regulations and relationships built on trust institutions need reconfiguration and new approaches in connection with which the basic principles of stability and sustainability have become insufficient. A significant decrease in the level of confidence in the business environment was reflected in the general global increase in prices, which is a consequence of the increase in transaction costs due to a decrease in the general level of confidence in the economic environment. Therefore, the institution of trust needs its scientific rethinking in the new realities of business functioning, such as the uncertainty of the new formation, digitalization, geopolitical risks and their consequences. The purpose of the article is the study of trust as an institution of business development in the new social challenge conditions and its importance in the business environment formation. The article examines the phenomenon of "trust in business" from a systemic point of view, as a basic institution in relations between subjects of economic relations. The multi-vector value of trust for business development is described. The functions of trust as the business environment institution and its importance in the formation of communication ties, both internal and external, were studied. The peculiarity of the trust institution as a business regulator of socio-economic interaction is determined. Various types of relationships that form trust in institutional architecture are considered, based on which a conclusion is made about the system-forming influence of trust on the institutional environment of business development. Various methods of assessing the level of trust development in business are systematized, and based on studies of the attitude to cryptocurrency as a new institution, the components of trust in the conditions of digitalization are described. The main ways to achieve trust are the development of relations between business, the state and the public, the identification of responsibility and ethics in the enterprise activities, as well as openness and honesty in reporting on one's activities. The use of such trust development tools leads to a synergistic effect on business development, the socio economic effect of which is based on reduced transaction costs, increased profitability, customer loyalty and improved institutional business interaction in general.
Keywords: Ключові слова: довіра, розвиток бізнесу, інституційне середовище, мультиплікатор довіри, бізнес-се редовище, флуктуації